Lamellar ichthyosis presenting as bilateral spontaneous corneal perforation - Chaudhary, M; Shrestha, GB; Keyal, A (Nepalese Journal of Ophthalmology, 2013)
Introduction: Lamellar Ichthyosis is an autosomal recessive, inherited skin disorder characterized by thickening, fissuring and scaling of the skin. Objective: To report a case of lamellar icthyosis and highlight the importance of monitoring corneal health in these patients. Case: We report a rare case of bilateral spontaneous corneal perforation in a patient with lamellar ichthyosis .The patient presented with complaints of diminution of vision, foreign body sensation, watering and discharge in both of his eyes for the last three months followed by pain and redness for one week. Visual acuities were light perception in both the eyes. Cicatricial ectropion was seen in both the lower eyelids. Corneal perforation was seen in both the eyes. Lamellar ichthyosis was diagnosed on the basis of scaling and excessive dryness of the entire body skin and was confirmed by skin biopsy. Peneterating keratoplasty of both eyes was done with cataract surgery of the right. The systemic anti-ichthyosis therapy was started. Ectropion of the right eye was corrected, and on follow-up at three months, the patient had a visual acuity of 4 /60 and CFCF in the right and the left eye respectively. Conclusion: In patients with cicatricial ectropion and dry eye secondary to ichthyosis, corneal health should be closely monitored because of the perforation risk. Nepal J Ophthalmol 2013; 5(9):117-119 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7838